Molecular characterization of Clostridium difficile isolated from carriage and association of its pathogenicity to prevalent toxic genes. (July 2018) - Abuderman, Abdulwahab Ali; Mateen, Ayesha; Syed, Rabbani; sawsan aloahd, Mustafa
Abstract: Background: There are reports of non-toxigenic C. difficile strains from asymptomatic carriers are increasing source of transmission. Asymptomatic carriage transmission in the hospital or community settings might have changed over the years. Therefore, we initiated a prospective epidemiological study to define the risk factors and pathogenicity of asymptomatic C. difficile carriage. Methods: Stools sample from 188 subjects with diarrhoea due to C. difficile toxin and colonization without diarrhoea was subjected to routine microbial culture, molecular characterization for identification of toxin genes and mechanisms of resistance in C.difficile . Demographic data were recorded. Fifty five were positive for C. difficile includes thirty nine toxigenic C. difficile (TCD) and sixteen non toxigenic C. difficile (NTCD) isolates. Pathogenecity of toxic and nontoxic strains were analysed using AO/EB staining, Annexin V staining using flow cytometer and Galleria mellonella survival analyses. Results: Among 188, fifty five were positive for C.difficile. Infected or colonized individual with TCD or NTCD were more frequently exposed to hemodialysis compared with uncolonized patients. Isolates showed more resistant to clindamycin and levofloxacin. All TCD and eight of NTCD were tcdA-positive. Only four of TCD were positive for cdtA, tcdA, and tcdB (7%, n = 55). In thirty isolates erm (B) gene was found to be prevelant gene. High virulence was found with TCD strain and it was validated using in Galleria mellonella infection model which supported in vitro experiments. The strain with cdtA, tcdA, and tcdB, seen to have elevated virulence to increased resistance and virulence subsequently led to raised virulence in this pathogen. Conclusion: Asymptomatic TCD colonization was relatively high, however, with a small number of enrolled subjects the significant of results might have limitations and the occurrence of CDI among different age group still remains unclear. Highlights: Infected or colonized patients with TCD or NTCD were frequently exposed to hemodialysis compared with uncolonized. High virulence was found with TCD strain and Galleria mellonella infection model supported in vitro experiments. The strain with cdtA, tcdA, tcdB, had increased resistance subsequently led to raised virulence in this pathogen. Asymptomatic TCD colonization was relatively high, however, the significant of results might have limitations.